Quelles représentations du quartier idéal à La Réunion ? Une réflexion sur les modes d’habiter et la qualité de vie comme indicateurs de la durabilité urbaine - Amandine Junot; Jean-Philippe Praene (Développement Durable et Territoires)
Through representations of ideal neighborhood, this research aims at exploring way of living and quality of life in Reunion Island, in order to better understand spatial and social behaviors and take them into consideration on sustainable lifestyle. 55 semi-structured interviews were performed and have been analyzed by the Iramuteq textual analysis software, supplemented by a manual content analysis. The results highlight that the representations were related to outdoor lifestyle where nature and community are crucial and could influence the perception of new sustainable objects as density, passive building, soft mobility or social cohesion.